Lichenochemical Analysis and Cytotoxicity of Diploschistes ocellatus (Fr.) Norman - Mahdieh Eftekhari; Mohammad Sohrabi; Majid Balaei Kahnamoei; Fatemeh Oskou; Helia Abdshahzadeh; Mahboubeh Mansourian; Mina Saeedi; Mohammad Reza Shams Ardekani; Tahmineh Akbarzadeh; Mahnaz Khanavi* (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Diploschistes ocellatus (Fr.) Norman is a valuable lichen possessing various biological properties which has been traditionally used by indigenous people in southwest of Iran in the treatment of different disorders. The aim of the current study was to evaluate cytotoxicity of different fractions of D. ocellatus against breast cancer cell lines through MTT assay, as well as lichenochemical analysis of the most potent fraction. Also, ducking study was performed to investigate the isolated compounds-protein interactions. Methods: In this work, aqueous, acetone, chloroform, ethyl acetate, and methanol fractions of D. ocellatus were evaluated against three breast cancer cell lines (MCF-7, T-47D, and MDA-MB-231) via MTT assay. Furthermore, docking was performed using the routine method and default parameters of the AutoDock 4.2 software. Results:  The acetone fraction depicted the most potent cytotoxicity and was candidate for lichenochemical analysis, leading to the isolation and identification of stictic acid and 2-(7'-hydroxy-3,5,6,8-tetramethyl-9-oxooxonan-2-yl) propanoic acid. Docking study of isolated compounds based on the inhibition of survivin, revealed desired interactions with that of amino acid residues. Conclusion: Based on the obtained results, D. ocellatus can be considered as a natural source of biologically active compounds and complementary studies are in high demand.